Альтернативна семіотизація місць пам’яті як маркер інтелектуального сюжету в "Мануалі до черепахи" Т. Савченко - Ганошенко, Юрій Анатолійович; Ganoshenko, Yu. A. (Миколаїв : Вид-во ЧНУ ім. П. Могили, 2019)
Стаття присвячена дослідженню особливостей ресеміотизації відомих місць пам’яті як частини авторської стратегії Тетяни Савченко щодо конструювання особливого типу ідентичності персонажа – стигматизованої й розщепленої. Сучасна авторка деконструює традиційні метажанрові схеми сімейної саги, травелогу й дитячої літератури, що в поєднанні з досить складною хронотопною моделлю (часта зміна часових прямих оповіді, гранично розімкнений простір, калейдоскопічність міст і місць пам’яті) та розгалуженою персонажною сферою (поліфонічність і взаємонакладання дискурсів, різні форми оповіді, дублювання імен і сюжетних варіацій однакових мотивів) створює художній ефект фрагментованої дійсності, у рецепції якої лакунарність відіграє не менш важливу роль, ніж внутрішня (психологічна) чи зовнішня подієвість. Несправжність зображених «місць пам’яті», інтелектуальна гра з читачем щодо їхньої автентичності та тожсамісних регіональних моделей, із ними пов’язаних, створюють ефект подвійної фікційності реальності, що робить «Мануал до черепахи» яскравим зразком сучасної української феноменологічної прози. The article is devoted to the study of the peculiarities of the alternative re-semiotisation of known places of memory in the novel by the Ukrainian author Tatiana Savchenko, The User Manual for the Turtle (2013). The aim of this study is to analyze the author‟s strategy of using the poetics of alternativity to construct an intellectual plot. The use of hermeneutic, phenomenological and psychoanalytical methods makes it possible to study the problem of alternative poetics in a work of art. Tatiana Savchenko designs a special type of character identity – split and stigmatized. The writer consistently deconstructs the traditional contemporary meta-genres of family saga, travelogue and children‟s literature. The work contains a complex chronotope model with frequent changes of temporal direct narratives, open space, appeal to numerous places of memory. The peculiarity of the structure of the work is an extensive personal sphere: the interchange of narratives, polyphonicity, duplication of names and tautological motives. Such a strategy creates a fragmented reality effect. Compositional lacunae are of no less importance for the reception of the work than psychological or external events. The places of memory in the novel are fictitiously presented, the author uses a sophisticated intellectual game with the reader about their authenticity. The cultural objects depiction can make the reader completely different. The multi-genre and poly-stylistic nature of the novel and its intricate symbolic nature make The User Manual for the Turtle a vivid example of contemporary Ukrainian phenomenological prose.
Alternative semiotization of memory as a marker of the intellectual plot in The user manual for the turtleby T. Savchenko
Keywords: поетика альтернативності; місця пам’яті; ідентичність; інтелектуальний сюжет; фрагментація; гра; poetry of alternativity; places of memory; identity; intellectual plot; fragmentation; game